2015
DOI: 10.15285/ebd.98899
|View full text |Cite
|
Sign up to set email alerts
|

Eğitim Fakültesi Öğrencilerinin Öznel İyi Oluş Düzeyleri ile Tinsellik, İyimserlik, Kaygı ve Olumsuz Duygu Düzeyleri Arasındaki İlişki

Abstract: demografik bilgilerini elde etmek için araştırmacı tarafından geliştirilen "Kişisel Bilgi Formu" kullanılmıştır. Bağımsız gruplar arasındaki farklılıkların testi için Mann-Whitney U Testi ve Kruskal-Wallis Testi kullanılmıştır. Öznel iyi oluş ile psikolojik değişkenler arasındaki ilişkiyi belirlemek için Spearman's rank order korelasyon yöntemi kullanılmıştır. Araştırmada elde edilen bulgulara göre üniversite öğrencilerinin öznel iyi oluş düzeyleri ile araştırmaya konu olan psikolojik değişkenler arasında anla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
(22 reference statements)
0
6
0
5
Order By: Relevance
“…Although in relevant literature happiness is depicted as the state of subjective well-being [21] it entails a more generic meaning, than only subjective well-being [22]. Thus, happiness as a concept refers to an individual's sense of contentment in both cognitive and emotional dimensions [23]; domination of positive feelings in an individual's life and a low level of negative feelings [24]; a subjective evaluation process in which the criteria are determined by the concerned individual [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although in relevant literature happiness is depicted as the state of subjective well-being [21] it entails a more generic meaning, than only subjective well-being [22]. Thus, happiness as a concept refers to an individual's sense of contentment in both cognitive and emotional dimensions [23]; domination of positive feelings in an individual's life and a low level of negative feelings [24]; a subjective evaluation process in which the criteria are determined by the concerned individual [25].…”
Section: Introductionmentioning
confidence: 99%
“…Again, in some studies in which the happiness levels of students are examined, positive emotional variables are positively correlated with life satisfaction, spirituality and optimism, there was a negative relationship between trait anxiety, state anxiety and negative emotions [50]. It is seen that the happiness levels of the students are above the average level of happiness in Solmaz [39], Şahin [40], Saygın and Arslan [41], Karahan, Dicle and Eplikoç [42] and Çevik and Yıldız's [43] in their study, students appear to be of above average levels of happiness.…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Bulk of research revealed that there was a gender difference in terms of subjective wellbeing (Cenkseven & Akbaş, 2007;Dilmaç & Bozgeyikli, 2009;İlhan, 2005;Yavuz-Güler & İşmen-Gazioğlu, 2008;Tümkaya, 2011;Gündoğdu & Yavuzer, 2012). Other studies found that students' type of academic major was linked to subjective wellbeing (Gündoğar, 2007;Öztürk & Çetinkaya, 2015). Students' types of living arrangements were also evidently associated to their subjective wellbeing (Chow, 2005;Çetinkaya, 2013).…”
Section: Extended Abstract Introductionmentioning
confidence: 96%
“…Students' types of living arrangements were also evidently associated to their subjective wellbeing (Chow, 2005;Çetinkaya, 2013). Health status in relation to college students' subjective wellbeing was a lessresearched variable, with findings providing support for a positive link between being healthy and happy (Öztürk & Çetinkaya, 2015;Çetinkaya, 2013;Pettit, 2001).…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation